A critique on the implementation of the housing policy through housing projects as a means to alleviate homelessness and poverty in the Northern Province, with specific reference to the Mhinga Housing Project - Mutshinyali, I. P. (University of the North, 2001)
Refer to document
Thesis (M.Dev.) --University of the North, 2001
Keywords: Housing policy; Housing projects; Homeless; Poverty alleviation; Northern Province; Mhinga Housing Projects; Government policy -- South Africa -- Limpopo Province; Policy-making -- Housing -- South Africa.; Service delivery -- Housing -- South Africa